1995
DOI: 10.1002/hep.1840210627
|View full text |Cite
|
Sign up to set email alerts
|

Roles of prostaglandin production and mitogen-activated protein kinase activation in hepatocyte growth factor—mediated rat hepatocyte proliferation

Abstract: Hepatocyte growth factor (HGF) and epidermal growth factor (EGF)-stimulated DNA synthesis in primary cultured rat hepatocytes. HGF-induced DNA synthesis was concentration-dependently inhibited by a cyclooxygenase inhibitor, indomethacin. BW755C, a dual inhibitor for cyclooxygenase and lipoxygenase activities, also inhibited hepatocyte growth. Prostaglandin E1 (PGE1), PGE2, and PGF2 alpha induced DNA synthesis even at such a low concentration as 5 nmol/L and potentiated [3H]thymidine incorporation induced by HG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
47
0

Year Published

1996
1996
2007
2007

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 37 publications
1
47
0
Order By: Relevance
“…In HGF-stimulated hepatoported following HGF receptor activation. [17][18][19][20][21][22][23] In the previous cytes, butanol prevented the formation of PA and DG.reports, 19,23 we showed that HGF stimulated inisitol 1,4,5-A PAP inhibitor, propranolol, inhibited DG production trisphosphate formation and increased in intracellular Ca 2/ with a reciprocal increase of PA, implying that PLD concentration. In contrast to rapid and transient change of played a role in the formation of not only PA but DG.…”
mentioning
confidence: 87%
See 4 more Smart Citations
“…In HGF-stimulated hepatoported following HGF receptor activation. [17][18][19][20][21][22][23] In the previous cytes, butanol prevented the formation of PA and DG.reports, 19,23 we showed that HGF stimulated inisitol 1,4,5-A PAP inhibitor, propranolol, inhibited DG production trisphosphate formation and increased in intracellular Ca 2/ with a reciprocal increase of PA, implying that PLD concentration. In contrast to rapid and transient change of played a role in the formation of not only PA but DG.…”
mentioning
confidence: 87%
“…In contrast, daidzein 41 which lacks the hydroxyl group of genistein and has minimal effect on tyrosine kinase activity, was without inhibitory effect on HGF-induced PLD activation. A cyclooxygenase inhibitor, indomethacin (50 mmol/L), which suppressed HGF-induced [ 3 H]thymidine incorporation in rat hepatocytes, 21 did not affect HGF-stimulated PLD activation. Effects of Ca 2/ on HGF-Induced PLD Activation.…”
Section: Effects Of Inhibitors For Pkc Ptk and Cyclooxygenase Onmentioning
confidence: 99%
See 3 more Smart Citations